Application of the frequency analysis of acoustic emission in the study of the metal alloy solidification - GOLEC, M.; GOLEC, Z. (Archives of Acoustics, 2000)
A frequency analysis of the acoustic emission signals was applied for the investigation of the solidification of a Pb-Sb alloy. Spectra of continuous emission and short-time acoustic emission impulses were investigated. It has been stated that, together with structural changes of the Pb-Sb alloy, significant changes occur in the spectra of the acoustic emission impulses generated in different phases of solidification. Less significant changes were observed in continuous acoustic emission spectra.